Study on the drying characteristics of green pellets of ultrafine iron ore concentrate - Wen B.-L.; Zhang X.-P.; Liu D.-L.; Li J.-X.; Sun X.-D.; Yang J.-L. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Ultrafine iron ore concentrate pose challenges such as poor pellet formation performance, low-bursting temperature, and a complex drying thermal regime. To examine the drying characteristics of green pellets made from ultrafine iron ore concentrate, the Weibull distribution function and Dincer model were employed to fit and analyze the corresponding drying curve. The effects of drying temperature and air speed on the strength of dried pellets were also studied. The findings revealed that the drying process of green pellets of ultrafine iron ore concentrate involved three stages: ascending speed, constant speed, and descending speed. As the drying temperature and air speed increased, the drying time decreased. The coefficient of determination R2 for the fitted Weibull distribution function model ranged from 0.995 to 0.998, while the R2 value for the Dincer model ranged from 0.990 to 0.996. Both fitted models aligned with the experimental data and proved to be effective. According to the Bi values obtained through the Dincer model, raising the drying air speed in the initial stage and the drying air temperature in the subsequent stage of the drying system could efficiently remove moisture, reduce the risk of green pellet rupture, and maintain productivity. The moisture diffusion coefficient and convective mass transfer coefficient increased with rising temperature and air velocity, following the order of Deff > Dcal > D*eff as determined by the Weibull distribution function, Dincer model, and Fick’s second law. Additionally, the activation energy value of ultrafine iron ore concentrate for drying derived from the Arrhenius formula was 4515.60 J/(mol·K). Notably, increasing the drying temperature increased the strength of the dried particles due to their more compact and dense internal structure. This study offers theoretical support for simulating the drying of green ultrafine iron ore concentrate pellets and provides guidelines for selecting diverse drying conditions and designing drying equipment.